Perancangan dan Pengembangan Sistem Administrasi Keuangan Berbasis Web Menggunakan Framework Laravel pada Bimba Aiueo Bintara IX - Nabila Balqis; Ranny Meilisa (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to design and develop a web-based financial administration system at Bimba AIUEO Bintara IX to address the problem of manual financial recording, which poses a risk of recording errors, delays in report preparation, and low efficiency in financial data management. This study uses the Research and Development (R&D) method with the Waterfall software development model, which includes the stages of needs analysis, system design, implementation, testing, and maintenance. The system was developed using the Laravel framework with a Model-View-Controller (MVC) architecture to support integrated management of income and expenditure data, and preparation of financial reports. System testing was conducted using the black box testing method to ensure all functions run according to user needs. The results of the study show that the developed system is able to automate the process of recording financial transactions, accelerate report preparation, and minimize data processing errors. In addition, financial information can be accessed in real-time, making it easier for managers to monitor and make decisions. Thus, the developed web-based financial administration system is proven to be able to improve the efficiency, accuracy, transparency, and accountability of financial management at Bimba AIUEO Bintara IX.